(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
The latest amendment to the CPA / 08 is one of the most demanding changes that accompanied the transposition of the EU Directive into our national legislation. Although more than one directive is concerned, the most significant is the Directive of the European Parliament and Council Directive 2013/48 / EU on 22 October 2013., on access to the lawyer in criminal proceedings and in proceedings based on a European Arrest Warrant, as well as on the right to third party information in the event of arrest and a right to communication with third parties and consular authorities. In essence, the Directive amended the police’s conduct towards the suspect in a way that “forbids” the gathering of information from the suspect, and the police are obliged to conduct the investigation with the full guarantee of the right to defense. Considering the practical aspect of the current legislation, especially when conducting criminal investigations into the domain of general criminality (blood and property delicts), for police officers, the informal testimony of the suspect plays a significant role in further prosecuting and directing criminal investigation. Directing the investigation is important for detecting potential perpetrators of crime, finding objects and traces that have resulted from the perpetration of a criminal offense or from those used to commit a criminal offense, ie information, objects and traces that might be of use to successfully conduct criminal proceedings. With the Amendments to the CPA / 08, police officers will no longer be able to conduct such informal informational conversation with the suspect for a specific criminal offense. The basic aim of the research is to establish which changes do the amendments to the legal provisions have on the detective and the demonstration activity of the police, and from a practical aspect, the research aims to look at the difficulties as well as the benefits faced daily by the police officers in detecting and proving the perpetration of criminal offenses. This paper presents the results of preliminary research conducted in the area of Zagreb County Police Administration.